Spatial Isoforms Reveal the Mechanisms of Metastasis - Yin Yin; Yuhao Wang; Xiao Yu; Yang Li; Yahui Zhao; Yanfeng Wang; Zhihua Liu (Advanced Science)
Abstract In esophageal squamous cell carcinoma (ESCC), lymph node (LN) metastasis is associated with poor survival. Emerging evidence has demonstrated elevated CD8+ T‐cell levels in metastatic LNs following immunotherapy and increased chemoresistance. However, the underlying regulatory mechanisms of CD8+ T cells in chemoresistant/metastatic patients have not been elucidated. Given that metastasis is linked to aberrant splicing patterns, transcripts with alternative splicing forms also play a critical role. With spatial transcriptomics (ST), spatial isoform transcriptomics (SiT), single‐cell RNA sequencing (scRNA‐seq), and T‐cell receptor (TCR) sequencing, the spatial isoforms are analyzed quantitatively in human solid tumors and LNs. These isoforms are classified according to expression and spatial distribution patterns and proposed that the temporal heterogeneity in isoforms is attributed to isoform biogenesis dynamics. C1QC+ tumor‐associated macrophages (TAMs) contribute to the formation of metastases in the context of both immunotherapy and chemotherapy. Additionally, CD74 isoforms can be targeted by mRNA drugs, such as antisense oligonucleotides (ASOs) and RNA interference (RNAi), to prevent chemoresistance and metastasis. Overall, this work suggests that C1QC+ TAMs interact with CD8+ CXCL13+ Tex cells via enrichment with the CD74 isoform in the ESCC ‘s metastatic lymph node.